Comment on “Transformation of educational introspection: evaluation of the current situation and development of basic music education in China” - Wenting Kong (Trans/Form/Ação)
Commented article: FENG, Y. N.; PENG, J. Transformation of educational introspection: evaluation of the current situation and development of basic music education in China. Trans/Form/Ação: Unesp journal of philosophy, v. 47, n. 5, p. e02400169, 2024. Available at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/15091.